Using the Bayesian approach to study the diet of Atlantic moonfish, Selene setapinnis (Teleostei: Carangidae) a new analysis proposal - Gorni, Guilherme Rossi; Loibel, Selene (Arquivos de Ciências do Mar, 2013)
This work aimed to study the diet of Atlantic moonfish, Selene setapinnis , on the Bayesian approach. Specimens were collected during fishing cruises accomplished by bottom trawling boats in the Itaguá Bay (Ubatuba, São Paulo State). All registered stomach material was classified in four alimentary categories: teleost fish, cephalopod molluscs, crustacean and vegetal remains. The numeric percentage of each alimentary category was the base of the Bayesian inference, adopting the Jeffreys method for obtaining the non-informative a priori distribution. 496 alimentary items were registered; the category composed by crustaceans was responsible for approximately 90% of diet, being characterized as primary resource of juvenile S. setapinnis . Due to low values in the proportion of the registered gastric content, teleost fish, cephalopod molluscs, crustacean and vegetal remains are characterized as accidental prey. The use of Bayesian approach comes as an alternative to the traditional methodology.